You are here:

- Home
- Science
- Mathematics
- Advanced Math
- Janet Yang

I can answer questions in Algebra, Basic Math, Calculus, Differential Equations, Geometry, Number Theory, and Word Problems. I would not feel comfortable answering questions in Probability and Statistics or Topology because I have not studied these in depth.

I tutor students (fifth through twelfth grades) and am a Top Contributor on Yahoo!Answers with over 24,000 math solutions.

Co-author of An Outline of Scientific Writing: For Researchers With English as a Foreign Language

I have a Bachelor's degree in Applied Mathematics from the University of California at Berkeley.

George White Elementary School. Homework Help program at the Ridgewood Public Library, Ridgewood, NJ. Individual students.

User | Date | K | C | P | Comments |
---|---|---|---|---|---|

Randy | 03/12/17 | 10 | 10 | 10 | Friendly, prompt, helpful response !! |

Randy | 12/04/16 | 10 | 10 | 10 | Friendly, helpful, courteous response !! |

Randy | 10/15/16 | 10 | 10 | 10 | Courteous, friendly, helpful response !! |

Randy | 09/12/16 | 10 | 10 | 10 | Friendly, helpful, courteous response !! |

Randy | 08/30/16 | 10 | 10 | 10 | I am not familiar with derivatives of ..... |

I disagree that ratios must use the same units. A common example is the ratio of boys to girls in a classroom, which clearly uses different units. While you can say "8 mm to 5 ft," it is better to use

area of metal = y² area of wood = x²-y² y²:(x²-y²) = 25:39 39y² = 25(x²-y²) = 25x² - 25y² 64y² = 25x² y² = (25/64)x² y = √((25/64)x²) = (√25/√64)√x² = (5/8)x w = (x - y)/2

B = mA C = A+B By substitution, C = A + mA. By the distributive rule, A + mA = A(1+m). ::::: D = C+B By substitution, D = A(m+1) + mA. By the distributive rule, D = A(2m+1). It is given that

"A, B, C, and D invest $s." A+B+C+D = s "B invests m times as much as A" B = mA "C invests as much as A and B combined" C = A+B = A+(mA) = A(m+1) "D invests as much as C and B combined" D

sec⁶θ - tan⁶θ - 3sec²θtan²θ = (sec²θ -tan²θ) (sec⁴θ + sec²θtan²θ + tan²θ) - 3sec²θtan²θ = ((1+tan²θ) - tan²θ) (sec⁴

Advanced Math

Answers by Expert: